Pelatihan Pembuatan Kemasan dan Pemasaran Produk Olahan UMKM di Kecamatan Martapura Barat - Fitriyanti Fitriyanti; Nurbidayah Nurbidayah; Depy Oktavian Akbar; Faradilla Iedliany; Gusti Khairunnisa (I-Com: Indonesian Community Journal, 2024)
Utilizing the herbal potential of kelakai and empon-ompon which have many health benefits can be applied to support health, one of which is by making processed products that are practical, healthy and safe. Previously, training had been carried out on the production of processed kelakai and empon-empon powders and tea dips, but regarding packaging and marketing, the information was still limited. The aim of this community service is for participants to: 1) understand more deeply the development of processed products; 2) Produce competitive products and market them in a modern way; 3) Understand good labeling and packaging. The activity was held on May 22 2024 at the Sungai Rangas Village Hall, West Martapura. The activity method is outreach through presentations related to entrepreneurship, how to make good product packaging and online marketing practices. The activity was attended by 10 people from the community of Sungai Batang village. The results obtained were that participants understood the importance of making products with attractive labels and packaging. Apart from that, participants also understand how to apply their social media for promotional media and apply other supporting marketing applications.